Speaking the culture: understanding the micro-level production of school culture through leaders' talk. Issue 3 (4th May 2018) - Harris, Jess
ABSTRACT: Global contexts of accountability have placed unprecedented pressure on school leaders to improve the performance of their schools. Despite recognition that leaders' influence is mediated by school culture, few studies offer systematic examinations of culture-in-action in schools. The concept of culture remains nebulous and is frequently glossed over as being 'messy' in studies of school change. This paper uses tools from membership categorisation analysis to demonstrate how culture is produced at a micro-level in and through the actions of leaders in one school. My analysis shows a disjuncture between the purported values and policies of the school and the ways that school leaders through their talk construct and implement school practices, and thus the culture-in-action at their school. I argue that implementing effective change is impossible without understanding and disrupting the micro-level production and reproduction of culture in schools.